Evaluation of the Factors Associated with AIDS Prevention Performance among Male Barbers Based on the Health Belief Model in Fasa - Ali Khani-Jeihouni; Saeed Ranjbari; Zahra Khiyali; Zahra Moradi; Mohammad Javad Motamedi (Hamadan University of Medical Sciences, 2017)
Background and Objectives: The number of patients inflicted with AIDS is on a growing trend in Iran, and one of the routes of disease transmission is the infection of sharps that are used for different people without disinfection. This study was designed to evaluate the performance of male barbers regarding AIDS prevention based on the Health Belief Model in Fasa, Iran. Materials and Methods: This cross-sectional study was conducted in 2014 on 220 male barbers working in Fasa, Iran. The participants were chosen through random multi-stage sampling. The data were collected using a researcher-made questionnaire including demographic data, knowledge, and constructs of the Health Belief Model using self-report. To analyze the data, linear regression was run in SPSS, version 18. Results: Our findings showed that among the participants, knowledge was good, perceived sensitivity was moderate, perceived severity was low, perceived benefits were high, perceived barriers were low, and practice was at a good level. Knowledge, perceived sensitivity, and perceived benefits constructs were predictors of barbers' performance in preventing AIDS. In general, 31.5% of variance predicted performance variables. Conclusions: Regarding the results of this study, by appropriate planning for raising awareness, perceived sensitivity, and perceived benefits regarding AIDS, barbers' performance can be enhances, which is essential for preventing and controlling AIDS.